Wildlife Logging Interactions in Tropical Forests Summary Statement of a Workshop Hosted by Wcs and Bolfor in Santa Cruz,Bolivia 13-15 November, 1996 - Robert A Fimbel (Media Konservasi, 1997)
Protected areas in the tropics are currently inadequate toprotect the biological diversity characterking this region, owingto their limited size, number, distribution, and composition.Within forested landscapes, production forests may containsignificant biodiversity not found within totally protected areas.In many countries, the large size and varied habitats of theseforests can complement the existing system of reserves, and taken as part of the landscape, can make significant contributions to biodiversity conservation. Current exploitation trends and practices within production forests however, have direct and indirect positive and negative impacts on many plant and animal species. Steps must be taken to improve our understanding of the effects of management practices on biological diversity, ways to mitigate negative aspects associated with them, and where our efforts should focus in the future to achieve ecological and economic sustainability of our natural resources.